THE EFFECT OF CHANGE MANAGEMENT ON THE FINANCIAL VIABILITY OF A HIGHER EDUCATION INSTITUTE IN SOUTH AFRICA (Singaporean Journal of Business Economics and Management, 2015)
This study was conducted at a higher education institute (herein referred to as the University) in South Africa. The aim of the research is to investigate the effect of change management on the financial viability and sustainability at the University. A review of the literature provides an understanding of the context, history, structure, rules, and regulations under which staff must work to understand the change for financial viability and sustainability. The theory is investigated to provide a context for understanding what knowledge, skills and attitudes will be perceived by the staff and how they will learn from this change management process. As a result, a strong human capital base with change-related knowledge and skills is a major source of competitive advantage.